INTRODUKSI TEKNOLOGI â€œMOTO KOH PADEEâ€: Studi Antropologi Pertanian di Aceh Utara - Saka, Putri Ananda (Department of Anthropology, 2018)
This study examines the introduction of Mooto Kooh Padeee technologyÂ to the community of Meurah Mulia, Aceh. The data obtained areÂ qualitative data using data collection techniques in the form ofÂ observation, in-depth interviews, data analysis, documentation studies,Â literature studies, and literature studies. While the theory used asÂ supporting analysis is Clifford Geertz's thinking about agriculturalÂ involution. The process of introducing and educating agriculturalÂ technology has begun to be intensively carried out in farmingÂ communities in rural Aceh. Including the District of Meurah Mulia,Â North Aceh District which experienced the introduction of Koh PadeeÂ moto harvesting technology. In the process of entering the innovation,Â of course experiencing various responses from the public. This is whatÂ is studied more deeply about how acceptance and rejection take place.Â Furthermore, the new value brought by the new technology hasÂ changed the pattern and culture of agriculture and the structure of itsÂ society. This is also analyzed in this study.